Pengembangan Perangkat Pembelajaran Berbasis Pendekatan Open-Ended untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa SMP - Nur Anwar; Rahmah Johar; Dadang Juandi (Didaktik Matematika, 2015)
Abstract. Mathematics is a lesson that is taught from primary education to higher education. However, the implementation of learning, especially SMP were encountered obstacles, one of which is the lack of representative learning device. This study was a response to the need for a valid learning tool, especially book teacher and student book. This research development, namely the development of learning tools based on open-ended approach to improve the ability to think creatively mathematical school students with materials Statistics. Software development models used in this study was a modification of the steps Plomp model, namely (1) preliminary investigation phase (phase preliminary investigation), (2) design phase (phase design), (3) realization/construction phase (phase realization/construction), and (4) test, evaluation, and revision phase (phase test, evaluation and revision. The device consists of learning learning implementation plan (RPP), teacher guide, student books, student worksheet and the test of learning outcomes. Methode of data collection was done through the validation sheet, test, and questionnaire of students responses. Results of the validation sheet was obtained that the RPP had an average value of 4.05 with valid criteria, teacher guide had an average value of 3.94 with valid criteria, students books had an average value of 3.9 with valid criteria, student worksheet had an average value of 3.83 with valid criteria, and test results of learning had an average value of 4.15 with very valid criteria. Students' response to the five components was as much as 94.3%.Keywords: Software development learning, model plomp, open-ended approach, mathematical creative thinking ability